Prototype Sistem Irigasi Subak berbasis Fuzzy Logic Menggunakan Wireless Sensor Network - Wardana, I Wayan Kayun; Widyantara, I Made Oka; Wirastuti, NMAE Dewi (Majalah Ilmiah Teknologi Elektro; Vol 19 No 2 (2020): (Juli - Desember) Majalah Ilmiah Teknologi Elektro, 2020)
Utilization of Information Technology in local Irrigation system in Bali called ‘Subak’ is expected to be able to distribute water evenly to all agricultural needs. Later, there will be no excess or even lack of water, no arable or infertile in the agricultural land due to water and its also expected to be able to produce maximum agricultural production. This study uses sensors of Soil Moisture, Soil Temperature and Soil pH which are expected to control water requirements for agricultural land which are flowed automatically by the system from the reports received by the sensor and the server using the Wireless Sensor Network. Water distribution will be carried out by the system after receiving water demand from sensors embedded in agricultural land using fuzzy logic so that the shared water will be the same as the Subak irrigation system but more controlled, effective and efficient. This may lead to better level of soil fertility required by plants as well as increase the agricultural output . The use of the Internet of Thinks (IoT) in this study will produce information that is fast and can be accessed on the Internet by using SmartPhone media, PCs or other communication devices.